Raden Panji Pulangjiwo Dalam Ludruk Lerok Anyar: Studi Kasus Bedah Folklor Pada Masyarakat Malang, Jawa Timur - Nois, Dea Cita Monita (Kusa Lawa, 2023)
Raden Panji Pulangjiwo Folklore is a folklore that exists in the Penarukan community, Malang. This folklore tells of the figure of Raden Panji Pulangjiwo who has a brave and courageous character against Mataram to defend the Kepanjen region. Because of the sacrifice of Raden Panji Pulangjiwo, he was willing to risk his life and died in Penarukan, Kepanjen. Thanks to the services and sacrifices of Raden Panji Pulangjiwo, his name was immortalized into the name of the southern region of Malang, named Kepanjen. Inspired by the folklore of Raden Panji Pulangjiwo, a ludruk group called Lerok Anyar led by Cak Marsam Hidayat re-represented the story of Raden Panji Pulangjiwo to be shown on the artistic stage in commemoration of the Birthday of the East Java Tourism and Culture Office at Taman Krida Budaya, Malang. This research is a qualitative descriptive study. This is due to the consideration of the data produced in the form of descriptive data, namely oral data and written data. This research was conducted using descriptive research methods with an ethnographic approach. The technique of determining informants was carried out by using purposive sampling method or selecting key informants. The data collection technique is qualitative in nature and emphasizes the study of a phenomenon in the Penarukan community that lives the folklore of Raden Panji Pulangjiwo in depth. After all the data has been collected, the next step is data analysis. In data analysis, researchers used interactive model data analysis according to Miles and Huberman.